Humanimals: Review of: Marta Segarra (2022): Humanimales. Abrir las fronteras de lo humano. Barcelona: Galaxia Gutenberg. - Pueyo Martín, Víctor (Analysis. Journal of Philosophical Research, 2022)
Review of: Marta Segarra (2022): Humanimales. Abrir las fronteras de lo humano. Barcelona: Galaxia Gutenberg.